The Cost of Underprivileged Children and Youth: a Value that should not be Ignored - Fuenglikhit, Hansachon; Phanthunane, Pudtan; Sooknark, Kanchit (Journal of Applied Economics and Management Strategy, 2024)
The academics article on “The cost of underprivileged children and youth: a value that should not be ignored” aimed to examine situations of the underprivileged children in Thailand and review the cost of underprivileged both in Thailand and aboard. This study was conducted with a documentary research method, and data were collected from online sources, literature, research documents, articles, and study reports of agencies related to underprivileged children. The finding revealed that the cost of underprivileged has been considerable to the government sector, personal costs, and economic opportunity costs. In the past, there has been an analysis of the costs of underprivileged children from various perspectives, both macro and micro. From a macroeconomic perspective, this analysis examined the economic and social costs of children and youth growing up in disadvantaged environments and the impact on the country’s overall GDP. From a microeconomic perspective, this analysis examined the costs of care, assistance, and social welfare for disadvantaged children and youth, as well as the economic opportunity costs resulting from lower expected lifetime earnings for this group. However, there has been no study of the overall size of the problem to enable policy makers to understand the economic and social losses that arise from the underprivileged of Thai children. Finally, this article presented the gaps in past studies and recommendations in order to further the empirical research in Thailand which will be useful for academic circles and policy recommendation in the future.